Evaluasi Atas Kesesuaian Penyajian Pendapatan Terhadap PSAK No. 30 Studi Kasus Pada Perusahaan Leasing PT. Swardharma Indotama Finance - Djanegara, H. Moermahadi Soerja; Elsyah, Elsyah (Jurnal Ilmiah Ranggagading (JIR), 2008)
The objective of this research is to find out acknowledgement method of income used by a company in accordance with finance accounting standard criteria (PSAK) No. 30. At PT Swadharma Indotama Finance, all incomes are acknowledged when they have been received. This matter indicates that the company has used cash basis method, except income from credit will be acknowledged in accrual basis way. Besides, accounting policy frame at PT Swadharma Indotama Finance is based on Indonesia Accounting Principle and follows the rules determined in PSAK. Based on profit loss accounting model at PT Swadharma Indotama Finance, it can be known that the profit and loss accounting model is single step: reporting and recording between income received and expense spent by the company must be separated. This one shows that PT Swadharma Indotama Finance follows the rules inPSAK No. 30, page 9, where income from rental trade is also reported as a main component at income cluster. Keywords: Reporting of income; PSAK No. 30.